Anda di halaman 1dari 12

# 1.

## For example: x² × x³, 2³ × 2⁵, (-3)² × (-3)⁴

In multiplication of exponents if the bases are same then we need to add the
exponents.

## Consider the following:

1. 2³ × 2²= (2 × 2 × 2) × (2 × 2) = 23+23+2 = 2⁵

2. 3⁴ × 3² = (3 × 3 × 3 × 3) × (3 × 3) = 34+24+2 = 3⁶

## 3. (-3)³ × (-3)⁴ = [(-3) × (-3) × (-3)] × [(-3) × (-3) × (-3) × (-3)] = (-

3)3+43+4 = (-3)⁷

4. m⁵ × m³ = (m × m × m × m × m) × (m × m × m) = m5+35+3 = m⁸

From the above examples, we can generalize that during multiplication when the bases
are same then the exponents are added.

aᵐ × aⁿ = am+nm+n

In other words, if ‘a’ is a non-zero integer or a non-zero rational number and m and n
are positive integers, then

aᵐ × aⁿ = am+nm+n

## Similarly, (a/b)ᵐ × (a/b)ⁿ = (a/b)m+nm+n

Note:

(i) Exponents can be added only when the bases are same.

(ii) Exponents cannot be added if the bases are not same like

m⁵ × n⁷, 2³ × 3⁴
For example:

1. 5³ ×5⁶

= (5 × 5 × 5) × (5 × 5 × 5 × 5 × 5 × 5)

## = 53+63+6, [here the exponents are added]

= 5⁹

2. (-7)1010 × (-7)¹²

= [(-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7)] × [( -7) × (-7)
× (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7) × (-7)].

## = (-7)10+1210+12, [exponents are added]

= (-7)²²

3. (1/2)⁴ × ( 1/2)³

## =[(1/2) × ( 1/2) × ( 1/2) × ( 1/2)] × [ ( 1/2) × ( 1/2) × ( 1/2)]

=(1/2)4+34+3

=(1/2)⁷

4. 3² × 3⁵

= 32+52+5

= 3⁷

5. (-2)⁷ × (-2)³

= (-2)7+37+3

= (-2)1010

6. (4/9)³ × (4/9)²

= (4/9)3+23+2
= (4/9)⁵

We observe that the two numbers with the same base are

For example:

## 3⁵ ÷ 3¹, 2² ÷ 2¹, 5(²) ÷ 5³

In division if the bases are same then we need to subtract the exponents.

## 7⁴ ÷ 7⁵ = 7⁴/7⁵ = (7 × 7 × 7 × 7)/(7 × 7 × 7 × 7 × 7) = 74−54−5 = 7−1−1

Let a be a non zero number, then

= a−2−2

## Thus, in general, for any non-zero integer a,

aᵐ ÷ aⁿ = aᵐ/aⁿ = am−nm−n

Note 1:

## Where m and n are whole numbers and m > n;

aᵐ ÷ aⁿ = aᵐ/aⁿ = a−(n−m)−(n−m)

Note 2:

## Where m and n are whole numbers and m < n;

We can generalize that if ‘a’ is a non-zero integer or a non-zero rational number and m
and n are positive integers, such that m > n, then

## aᵐ ÷ aⁿ = am−nm−n if m < n, then aᵐ ÷ aⁿ = 1an−m1an−m

Similarly, (a/b)ᵐ ÷ (a/b)ⁿ = (a/b)m−nm−n

For example:

1. 71010 ÷ 7⁸ = 7107871078
= (7 × 7 × 7 × 7 × 7 × 7 × 7 × 7 × 7 × 7)/(7 × 7 × 7 × 7 × 7 × 7 × 7 × 7)

## = 710−810−8, [here exponents are subtracted]

= 7²

2. p⁶ ÷ p¹=p⁶/p¹

= (p × p × p × p × p × p)/p

## = p6−16−1, [here exponents are subtracted]

= p⁵

3. 4⁴ ÷ 4² = 4⁴/4²

= (4 × 4 × 4 × 4)/(4 × 4)

= 4²

## = 10−(4−2)−(4−2), [See note (2)]

= 10−2−2

5. 5³ ÷ 5¹

= 53−13−1

= 5²
6. 3⁵/3²

= 35−25−2

= 3³

7. (-5)⁹/(-5)⁶

= (-5)9−69−6

= (-5)³

8. (7/2)⁸ ÷ (7/2)⁵

= (7/2)8−58−5

= (7/2)³

3. Power of a power
For example: (2³)², (5²)⁶, (3² )−3−3

(i) (2³)⁴

## Now, (2³)⁴ means 2³ is multiplied four times

i.e. (2³)⁴ = 2³ × 2³ × 2³ × 2³

=23+3+3+33+3+3+3

=2¹²

(ii) (2³)²

## Similarly, now (2³)² means 2³ is multiplied two times

i.e. (2³)² = 2³ × 2³

= 2⁶

(iii) (4−2−2)³

## i.e. (4−2−2)³ =4−2−2 × 4−2−2 × 4−2−2

= 4−2+(−2)+(−2)−2+(−2)+(−2)
= 4−2−2−2−2−2−2

= 4−6−6

## Note: Here, we see that -6 is the product of -2 and 3 i.e, (4−2−2)³ =

4−2×3−2×3 =4−6−6

For example:

1.(3²)⁴ = 32×42×4 = 3⁸
2. (5³)⁶ = 53×63×6 = 5¹⁸
3. (4³)⁸ = 43×83×8 = 4²⁴
4. (aᵐ)⁴ = am×4m×4 = a⁴ᵐ
5. (2³)⁶ = 23×63×6 = 2¹⁸
6. (xᵐ)−n−n = xm×−(n)m×−(n) = x−mn−mn
7. (5²)⁷ = 52×72×7 = 5¹⁴
8. [(-3)⁴]² = (-3)4×24×2 = (-3)⁸

In general, for any non-integer a, (aᵐ)ⁿ=am×nm×n = aᵐⁿ. Thus where m and n are
whole numbers.

If ‘a’ is a non-zero rational number and m and n are positive integers, then{(a/b)ᵐ}ⁿ
= (a/b) ᵐⁿ

For example:

[(-2/5)³]²

= (-2/5)3×23×2

= (-2/5)⁶
4. Multiplying powers with the same exponents

## For example: 3² × 2², 5³ × 7³

We consider the product of 4² and 3², which have different bases, but the same
exponents.

(i) 4² × 3² [here the powers are same and the bases are different]

= (4 × 4)×(3 × 3)

= (4 × 3)×(4 × 3)

= 12 × 12

= 12²

Here, we observe that in 12², the base is the product of bases 4 and 3.

We consider,

(ii) 4³ × 2³

=(4 × 4 × 4)×(2 × 2 × 2)

=8 × 8 × 8

=8³

## (iii) We also have, 2³ × a³

= (2× 2 × 2)×(a × a × a)

= (2 × a)×(2 × a)×(2 × a)

= (2 × a)³

## = (2a)³ [here 2 × a = 2a]

(iv) Similarly, we have, a³ × b³

= (a × a × a)×(b × b × b)

= (a × b)× (a × b)× (a × b)

= (a × b)³

aᵐ × bᵐ

= (a × b)ᵐ

(-a)³ × (-b)³

= [(-a)×(-b)]³

## = (ab)³ [here a × b = ab and two negative become positive,

(-) × (-) = +]

5. Negative Exponents
If the exponent is negative we need to change it into positive exponent by writing the
same in the denominator and 1 in the numerator.

## If ‘a’ is a non-zero integer or a non-zero rational number and m is a positive integers,

then a−m−m is the reciprocal of aᵐ, i.e.,

## a−m−m = 1am1am, if we take ‘a’ as p/q then (p/q)−m−m = 1/(p/q)ᵐ = (q/p)ᵐ

again, 1a−m1a−m = aᵐ

## Consider the following

2−1−1 = 1/2
2−2−2 = 1/2² = 1/2 × 1/2 = 1/4
2−3−3 = 1/2³ = 1/2 × 1/2 × 1/2 = 1/8
2−4−4 = 1/2⁴ = 1/2 × 1/2 × 1/2 × 1/2 = 1/16
2−5−5 = 1/2⁵ = 1/2 × 1/2 × 1/2 × 1/2 × 1/2 = 1/32

[So in negative exponent we need to write 1 in the numerator and in the denominator 2
multiplied to itself five times as 2−5−5. In other words negative exponent is the
reciprocal of positive exponent]

For example:

1. 10−3−3

= 110−3110−3, [here we can see that 1 is in the numerator and in the denominator 10³
as we know that negative exponent is the reciprocal]

## = 1/10 × 1/10 × 1/10 [here 10 is multiplied to itself 3 times]

= 1/1000

2. (-2)−4−4

= 1/(-2)⁴ [here we can see that 1 is in the numerator and in the denominator (-2)⁴]

= 1/16

3. 2−5−5

= 1/2⁵

= 1/2 × 1/2

= 1/4

4. 13−413−4
= 3⁴

=3×3×3×3

= 81

5. (-7)−3−3

= 1/(-7)³

6. (3/5)−3−3

= (5/3)³

7. (-7/2)−2−2

= (-2/7)²

## 6. Power with exponent zero

If the exponent is 0 then you get the result 1 whatever the base is.

## If ‘a’ is a non-zero integer or a non-zero rational number then,

a0 0 = 1

Similarly, (a/b)00 = 1

## a00 = 1 [anything to the power 0 is 1]

(a/b)00 = 1
(-2/3)00 = 1
(-3)00 = 1

For example:

1. (2/3)³ × (2/3)−3−3
= (2/3)3+(−3)3+(−3), [here we know that aᵐ × aⁿ = am+nm+n]
= (2/3)3−33−3

= (2/3)00

=1

2. 2⁵ ÷ 2⁵

= 2⁵/2⁵

= (2 × 2 × 2 × 2 × 2)/(2 × 2 × 2 × 2 × 2)

=2

=1

3. 400 × 300

## = 1 × 1, [here as we know anything to the power 0 is 1]

=1

4. aᵐ × a−m−m

= am−mm−m

= a00

=1

5. 500 = 1

6. (-4/9)00 = 1

7. (-41)00 = 1

8. (3/7)00 = 1
7. Fractional Exponent
In fractional exponent we observe that the exponent is in fraction form.

## 21515 =⁵√2 (fifth root of 2).

For example:

1. a1n1n, [Here a is called the base and 1/n is called the exponent or power]